THE INFLUENCE OF ESG METRICS ON INVESTOR BEHAVIOR AND DECISION-MAKING PROCESS THROUGH THE LENS OF MENTAL HEURISTICS - Heboyan, Arevik (Modern Psychology, 2025)
Investor decision-making is often shaped by research of a range of financial and non-financial parameters of the investee company for predicting investment profitability, understanding future risks and challenges associated with the product or market as a whole, creating a mental image/profile of the company with its advantages and disadvantages. Psychological research from the 1970s and on allowed us to conceptualize real-world decision-making (DM), understand the limitations of human information processing and the influence of personal cognitive, emotional features bounding our rationality, yet allowing us to make optimal decisions. The research gave us an understanding of cognitive mechanisms of heuristics and biases, which somewhat simplify the complex informational flow and optimize the process of mental analysis, yet can create some systematic errors or skewed perceptions of the situation or a sense of overconfidence. This study explores how ethical considerations function as heuristics in guiding investment behavior, particularly in the context of ESG (Environmental, Social, and Governance) performance. Drawing from behavioral finance theory, we hypothesize that ethical reputation acts as a cue that influences perceived trustworthiness, and depending on the intentions of the investor (fast gain or slow grow) can affect their decisions differently. Using a sample of 37 investors, we conducted a mixed-methods study combining decision-making and mental heuristics profile and personal DM factors with the self-perceived effectiveness of investment behavior and proneness to consider ESG metrics. The results demonstrate that long-term investors systematically utilize ESG data and, through the lens of heuristics and biases (the interconnection yet to be researched), impact DM. Ye,t considering ESG metrics important, the investors did not necessarily perform ESG information-seeking behavior. These findings highlight the intersection between ethics and cognitive processing in financial contexts. Ethical cues appear to serve as intuitive filters in investment judgments, suggesting that proper ESG reporting and communication may significantly shape market behavior through psychological channels.